Thermal stability and thermal decomposition of sucralose - de Almeida, Rafael Ramirez; Schnitzler, Egon; Bannach, Gilbert; Lacerda, Luis Gustavo; Cavalheiro, Éder Tadeu Gomes; Carvalho Filho, Marco Aurélio da Silva; Ionashiro, Massao (Eclética Química, 2009)
Several papers have been described on the thermal stability of the sweetener, C12H19Cl3O8 (Sucralose). Nevertheless no study using thermoanalytical techniques was found in the literature. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC) and infrared spectroscopy, have been used to study the thermal stability and thermal decomposition of sweetener.